Reading Attitude vs. Reading Strategy: Are they complementary? - Bernadette Lamsis Soliba; John Rey O Pelila; Denise Mae H Casuga; Justine Kayne M Villanueva; Mishelle G Bueno; Jemimah A Caligtan; Johnene E Catama; Pamela L Dagul; Ariel P Pangilinan (Journal of Language Education and Educational Technology (JLEET), 2020)
This study aimed at determining the reading strategies and reading attitudes employed by Senior High School students, at the same time to investigate whether the two variables are complementary and how they affect the reading comprehension of the students. The study employed a quantitative method. Through purposive sampling, 50 Grade-11 students of the University of the Cordilleras- Senior High School who were enrolled in the educational strand of Humanities and Social Sciences (HUMSS) of the Academic Year 2017-2018 were involved. The researchers used three instruments namely: Reading Attitude Survey (RAS), Reading Strategy Survey (RSS), and Reading Comprehension Performance Test (RCPT). The tests were conducted in two sessions: pre-test and post-test. Based on the findings, the students employed various reading strategies before, during and after reading that resulted to the improvement of their reading comprehension. It was also found out that the reading attitudes of the students turned positively through the use of the strategies, leading to a conclusion that reading strategies and reading attitudes are complementary